Process of Organizational Governance Maturity Model of Government Internal Supervisory Apparatus in Realizing Good Government in Sorong City - Laku, Ruddy Rudolph; Yunus, Muhammad; Haning, Thahir (KnE Social Sciences, 2025)
The organizational governance maturity model is used to measure the extent to which organizational governance is effectively implemented. This approach is important to be adapted in public sector organizations without exception to the Government Internal Audit Apparatus (APIP) organization, which has the main function of supervision to realize good governance. This research aims to explain the process of organizational governance maturity of the Government Internal Audit Apparatus in realizing good governance in Sorong City. This research uses a qualitative approach. Data collection methods include observation, in-depth interviews, and documentation. Data sources consist of primary and secondary data, while data analysis is carried out by stages of data reduction, data presentation, and conclusion drawing. The informants in this study were the Government Internal Audit Apparatus. The results of this study indicate that Sorong City APIP carries out the risk management process by identifying, analyzing, and responding to potential risks based on Sorong Mayor Regulation Number 8 concerning Risk management guidelines. In internal control, policies, audits, and SOPs are applied to prevent and detect irregularities. Code of ethics, such as integrity, objectivity, and professionalism, are implemented to maintain ethical standards. Vertical and horizontal communication is utilized in apparatus performance evaluation. Cooperation is established both internally between APIP units and externally with auditors, legislators, and executives. Constraints such as limited human resources and coordination are challenges, but the support of commitment and regulations strengthens synergy. In reporting, APIP seeks to convey governance and risk information in an integrative manner to stakeholders through periodic reports and strategic communication forums.